REY‐Th‐U Solute Dynamics in the Critical Zone: Combined Influence of Chemical Weathering, Atmospheric Deposit Leaching, and Vegetation Cycling (Mule Hole Watershed, South India). (11th December 2017) - Braun, Jean‐Jacques; Riotte, Jean; Battacharya, Shrema; Violette, Aurélie; Prunier, Jonathan; Bouvier, Vincent; Candaudap, Frédéric; Maréchal, Jean‐Christophe; Ruiz, Laurent; Panda, Smruthi Rekha; Subramanian, S.
Abstract: The source and proportion of REY, Th, and U exported by groundwater and by the ephemeral stream along with the elemental proportions passing through vegetation have been assessed in the subhumid tropical forested CZO of Mule Hole, Southern India. The study relies on a pluriannual hydrogeochemical monitoring combined with a hydrological model. The significant difference between the soil input (SI) and output (SO) solute fluxes (mmol/km 2 /yr) of LREE (SI‐SO = 13, 250‐1, 500), HREE (1, 930‐235), Th (64‐12), and U (63‐25) indicates a strong uptake by roots carried by canopy and forest floor processes. The contribution of atmospheric dust leaching can reach about 60% of LREE and 80% of HREE. At the watershed scale, the U solute flux exported by groundwater (180 mmol/km 2 /yr) mainly originates from the breakdown of primary U‐bearing accessory minerals and dominates by a factor of 25 the stream flux. The precipitation of authigenic U‐bearing phases and adsorption onto Fe‐oxides and oxyhydroxides play a significant role for limiting the U mobility. In the groundwater, the plagioclase chemical weathering is efficiently traced by the positive Eu‐anomaly. The very low (REY) to nil (Th) contents are explained by the precipitation of authigenic phases. In the stream flow, dominated by the overland flow (87% of the yearly stream flow), the solute exports (in mmol/km 2 /yr) of REY (1, 080 for LREE and 160 for HREE) and of Th (14) dominate those by groundwater. Their mobility is enhanced by chelation with organic ligands produced by forest floor and canopy processes. Key Points: Source of solute rare earths, thorium, and uranium in the Mule Hole tropical watershed has two main origins: heavy accessory bearing minerals and atmospheric dusts Rare earths and thorium, mainly from atmospheric dust leaching origin, are significantly recycled by vegetation and exported by overland flow as organic complexes Solute export by groundwater is much more significant for uranium than for rare earths and thorium, which transfer is limited by precipitation of secondary phosphates and oxides